Bentuk Ragam Bahasa Iklan Permen Kesehatan Pelega Tenggoorokan di Media Sosial - Rahayu, Cory; Inderasari, Elen (Ikaprobsi, 2024)
This research aims to describe the various forms of language and functions of advertising language on YouTube social media using sociolinguistic studies. The data source for this research is a video advertising health lozenges on YouTube social media. This research is included in qualitative descriptive research using sociolinguistic studies. Researchers will analyze the variety of languages in advertisements for health lozenges on YouTube social media. Data collection uses listening techniques, note-taking techniques and documentation techniques. The validity technique in this research uses source triangulation techniques. The data source for this research is a video advertising health lozenges on YouTube social media. In this study, 31 data were found in language varieties dominated by business language varieties, there were 17 data, 8 data from official language varieties, 5 data from casual language varieties and 1 data from familiar language varieties. Penelitian ini memiliki tujuan untuk mendeskripsikan bentuk ragam bahasa serta fungsi bahasa iklan pada media sosial youtube dengan menggunakan kajian sosiolinguistik. Sumber data penelitian ini adalah video iklan permen kesehatan pelega tenggorokan yang ada di media sosial youtube. Penelitian ini termasuk ke dalam penelitian deskriptif kualitatif menggunakan kajian sosiolinguistik. Peneliti akan menganalisis mengenai ragam bahasa pada iklan permen kesehatan pelega tenggorokan di media sosial youtube, Pengumpulan data menggunakan teknik imak, teknik catat, dan teknik dokumentasi. Teknik keabsahan pada penelitian ini menggunakan teknik triangulasi sumber. Sumber data penelitian ini adalah video iklan permen kesehatan pelega tenggorokan yang ada di media sosial youtube. Pada penelitian ini ditemukan 31 data dalam ragam bahasa didominasi pada ragam bahasa usaha terdapat 17 data, 8 data berasal ragam bahasa resmi, 5 data pada ragam bahasa santai dan 1 data ragam bahasa akrab.